Configurational Study Based on the Analysis of Homonuclear and Heteronuclear Coupling Constants - Cen-Pacheco, Francisco (2022)
A crucial step in the discovery of any new molecule is to determine its complete structure, which includes determining the planar structure of the molecule and its stereochemistry. It has been seen that the latter is strongly linked to its chemical and biological properties. However, this is particularly difficult when the chiral center(s) are in portions with high flexibility that are easily exchanged between different conformations, as is the case with acyclic fragments or rings with high flexibility. Improvements in NMR spectroscopy methods have made it a powerful tool for determining the structure of organic molecules. One of the most popular strategies developed in recent decades to address many structural problems is J-constant-based analysis (JBA), which consists of the use of long-distance heteronuclear (C—H) coupling constants (two or three bonds) to determine the stereochemistry, even in systems with flexibility.